2022
DOI: 10.1111/1759-7714.14543
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib restricts small cell lung cancer proliferation via reactive oxygen species‐mediated endoplasmic reticulum stress

Abstract: Background: Pazopanib is an approved multitarget anticancer agent for soft tissue sarcoma (STS) and renal cell carcinoma (RCC), which is also under clinical investigation for other malignancies, including small cell lung cancer (SCLC). However, the potential anti-SCLC mechanisms of pazopanib remain unclear. Methods: Cell viability was evaluated by CCK-8, apoptotic cell detection was conducted using annexin V/PI staining followed by flow cytometry, and Western blot analysis was used to detect the apoptotic-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A widely documented series of small molecule drugs and chemotherapeutic agents induce elevation of ROS and ER stress in cancer cells, including bortezomib, sorafenib, as well as pazopanib, etc. [25,[34][35][36]. As there is no known effective target for pexidartinib in ATC cells, we hypothesize that pexidartinib achieves its antitumor effects by mediating excessive oxidative stress and ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…A widely documented series of small molecule drugs and chemotherapeutic agents induce elevation of ROS and ER stress in cancer cells, including bortezomib, sorafenib, as well as pazopanib, etc. [25,[34][35][36]. As there is no known effective target for pexidartinib in ATC cells, we hypothesize that pexidartinib achieves its antitumor effects by mediating excessive oxidative stress and ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pazopanib, a multitargeted tyrosine kinase inhibitor, which is known to induce ROS-mediated ER stress and apoptosis in lung cancer, was evaluated in a phase III trial as a maintenance therapy after standard first-line platinum-based chemotherapy in patients with advanced NSCLC [40]. However, this study was stopped because of a lack of efficacy based on strict progression-free survival (PFS) criteria at a futility interim analysis [41].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of toxicity of harmine in KYSE‐30 and EC‐9706 cells in our study is a limitation. Lots of studies have shown that anti‐cancer agents can trigger cell apoptosis via reactive oxygen species (ROS)‐mediated ER stress (Li et al, 2022; Liu et al, 2018; Yang et al, 2020), implying that ROS is upstream of ER stress. Recently, Sarita et al found that harmine‐induced generation of ROS leads to cell death (Sarkar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%